Foundations of Financial Management (United States of America. Irwin, Inc.)
"Foundations of financial management is commited to making finance accessible to the student. In fact, many pedagogical changes were made in the sixth edition with the objective of enhancing your students' learning. Significant content revision have also been made in order to maintain in the high quality that the market has come to expect from foundations of financial management. As always, in the sixth edition we remain strongly committed to presenting the concepts of finance in an enlightening and interesting manner".
Includes bibliographical references.
English text
Keywords: Financial management